188 IMPROVING THE ASSESSMENT AND MANAGEMENT OF FALLS IN OLDER PEOPLE BY THE EMERGENCY DEPARTMENT IN THE HOME. (18th November 2021) - Sheehan, M; Mulcaire, J; McNamara, R
Abstract: Background: Falls among older adults are the injury pattern that causes the most morbidity and mortality. Assessing and managing these in the patients' homes is challenging; it requires a comprehensive, systematic approach. This quality Improvement Project used a Comprehensive Geriatric Assessment for older adults who have suffered fall, carried out by an Emergency Department in the Home (EDITH) practitioner in the patient's home. Aim: To improve the evaluation and management of older people who have fallen and are attended to by the Emergency Department in the Home. Methods: This OD project was carried out using the HSE People's Needs Defining Change model. A new, streamlined version of the Comprehensive Geriatric Assessment tool was developed and introduced, and this was implemented and altered over two PDSA cycles. Results: Documentation of falls improved dramatically, from a median of three out of 12 domains included to a median of 11 domains included. Users' feedback helped the CGA evolve and was incredibly positive about the change. Conclusion: This project shows that a CGA can be used successfully in patients' own homes to assess risk factors for falling. The HSE's People's Needs Defining Change can be used to implement community-based projects. The community CGA tool could be explored by other areas and organisations in the future.